BS EN ISO 14819-3. Intelligent transport systems. Traffic and travel information messages via traffic message coding. Part 3. Location referencing for Radio Data System. Traffic Message Channel (RDS-TMC) using ALERT-C (27th August 2019) - British Standards Institution,
No abstract available